2018
DOI: 10.1377/hlthaff.2017.1153
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant Infection Treatment Costs Have Doubled Since 2002, Now Exceeding $2 Billion Annually

Abstract: Antibiotic-resistant infections are a global health care concern. The Centers for Disease Control and Prevention estimates that 23,000 Americans with these infections die each year. Rising infection rates add to the costs of health care and compromise the quality of medical and surgical procedures provided. Little is known about the national health care costs attributable to treating the infections. Using data from the Medical Expenditure Panel Survey, we estimated the incremental health care costs of treating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(114 citation statements)
references
References 18 publications
2
103
0
4
Order By: Relevance
“…Our analysis of Burnham and colleagues' recent study shows that “V09.x” ICD‐9‐CM codes had a (weighted) sensitivity of 11.9 percent vs the gold standard of laboratory cultures in accurately identifying patients with MDROs during hospitalization . Similarly, a nationally representative study by Thorpe and colleagues of patients with MDROs identified 12 percent of such MDRO patients via ICD‐9‐CM codes and the other 88 percent of MDRO patients via evidence of antibiotic drug treatment failure . These numbers are close to what we would expect if the numbers of undiagnosed cases of MDROs from Burnham and colleagues' study were generalizable to Thorpe and colleagues' nationally representative sample.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…Our analysis of Burnham and colleagues' recent study shows that “V09.x” ICD‐9‐CM codes had a (weighted) sensitivity of 11.9 percent vs the gold standard of laboratory cultures in accurately identifying patients with MDROs during hospitalization . Similarly, a nationally representative study by Thorpe and colleagues of patients with MDROs identified 12 percent of such MDRO patients via ICD‐9‐CM codes and the other 88 percent of MDRO patients via evidence of antibiotic drug treatment failure . These numbers are close to what we would expect if the numbers of undiagnosed cases of MDROs from Burnham and colleagues' study were generalizable to Thorpe and colleagues' nationally representative sample.…”
Section: Methodssupporting
confidence: 69%
“…MDROs are microorganisms that are resistant to one or more antimicrobial agents and are most often resistant to all but one or two antimicrobial agents . Most recently, a Thorpe and colleagues find that the share of bacterial infections that are associated with MDROs doubled between 2002 and 2014 in the United States . The last nationally representative hospital study found that hospitalizations with diagnoses for drug resistance increased 359 percent over the period 1997‐2006 .…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic use also increases the risk of other serious infections, such as Clostridium difficile, which can be life‐threatening and difficult to treat . Recent estimates suggest that treatment for antibiotic‐resistant infections costs the U.S. over $2 billion dollars annually . Overusing antibiotics also unnecessarily places patients at risk for antibiotic‐related side effects (eg, diarrhea) and allergic reactions…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent estimates suggest that treatment for antibioticresistant infections costs the U.S. over $2 billion dollars annually. 8 Overusing antibiotics also unnecessarily places patients at risk for antibiotic-related side effects (eg, diarrhea) and allergic reactions. 1 Previous research has identified several factors that contribute to antibiotic overuse.…”
mentioning
confidence: 99%
“…Згідно з даними GLASS (Глобальна система нагляду за стійкістю до антимікробних препаратів), опублікованими в 2017 році, щорічно антибіотикорезистентні штами зумовлюють гнійно-запальні процеси в 500 тис. осіб [3], а витрати на лікування пацієнтів у країнах ЄС сягають 7 млрд євро, у США -6,5 млрд доларів США [4][5][6]. За прогнозами аналітиків, до 2050 року смертність від інфекційних хвороб у Європі може скласти 400 тис.…”
unclassified